The status of serum cortisol before and after treatment of schizophrenia and its correlation to disease severity and improvement: A longitudinal study. (November 2021) - Woldesenbet, Yohannes Markos; Alenko, Arefayne; Bukata, Iyasu Tadesse; Gedefaw, Lealem; Fikru, Chaltu
Background: Hypothalamic–pituitary–adrenal axis functioning, with cortisol as its major output hormone, has been presumed to play a key role in the development of psychopathology of schizophrenia. Objective: We examined the association of serum cortisol with disease severity and improvement in schizophrenia patients in Jimma, Ethiopia. Method: A total of 34 newly diagnosed schizophrenics were included in this study. Data on demographic, behavioral, clinical state, serum cholesterol level, and antipsychotic usage were obtained at baseline and after 8 weeks. The Positive and Negative Syndrome Scale was used to assess psychotic symptoms severity. A paired sample t -test was used to compare baseline and post-treatment values. Linear regression was used to assess associations. Result: Post-treatment serum cortisol level was significantly lower than its baseline value ( p = 0.001). There was also a significant positive and negative psychotic symptoms decrease after treatment (baseline positive psychotic vs post-treatment positive psychotic symptoms: t (33) = 6.24 (95% confidence interval = 7.03, 13.84, p = 0.000) and (baseline negative psychotic vs post-treatment negative psychotic symptoms: t (33) = 4.21 (95% confidence interval = 3.82, 10.99, p = 0.000). At baseline, neither positive nor negative subscore on the Positive and Negative Syndrome Scale showed an association with serum cortisol level ( B = −0.016, p = 0.794 and B = −0.032, p = 0.594). However, serum cortisol level showed strong associations with post-treatment positive sub scores and negative sub scores ( B = 0.167, p = 0.007) and ( B = 0.144, p = 0.010) on the Positive and Negative Syndrome Scale. Conclusion: We found a significant decrease in serum cortisol level after antipsychotics treatment and that was associated with improvement in psychotic symptoms in schizophrenics in Jimma, Ethiopia.